Skrining Fitokimia Dan Perbandingan Kadar Vitamin C Pada Buah Apel Impor Dan Buah Apel Lokal Yang Dijual Di Pasar Buah 88 Pekanbaru Menggunakan Metode Spektrofotometer UV-Vis: Phytochemical Screening and Comparison of Vitamin C Levels in Imported and Local Apples Sold at Pekanbaru 88 Fruit Market Using the UV-Vis Spectrophotometer Method - Lovera Anggraini; Nia Oktavia (LPPM Universitas Abdurrab, 2023)
Apple is a fruit that contains a lot of fiber to maintain intestinal health and smooth digestion. Apples also contain lots of low-calorie protein and high vitamin C. Vitamin C is a compound that is important for health and beauty because of its antioxidant properties. Vitamin C levels in apples vary depending on the type of environment and where they grow. The aims of this study were to determine secondary metabolites and to compare the levels of vitamin C in imported apples and local apples sold at 88 Fruit Market, Pekanbaru City. Phytochemical screening in the form of reaction tests color to determine the secondary metabolites of imported apples and local apples. Imported and local apples contain secondary metabolites in the form of flavonoids,alkaloids and tannins. Comparison of vitamin C levels using the UV-Vis Spectrophotometry method. The maximum wavelength of vitamin C obtained was 264 nm with an absorbance of 0.491. The linear regression equation is y=0.0794x- 0.0048. The results of a comparison of the levels of vitamin C in imported apples and local apples, imported apples 56.13 mg/100g and local apples 69.32 mg 100g.